Metode Penelitian Ilmiah Uji Keamanan Mikrobiologis Pisang Sale Khas Muaro Bungo sebagai Produk Pangan Siap Konsumsi - Ratu Zara; Ardi Mustakim (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
Bananas are a tropical fruit that is popular because of its sweet taste and high nutrient content. However, bananas have a major drawback, which is a short shelf life. After reaching perfect ripeness, the banana will undergo a change in mushy texture, the skin will appear black spots, and there will be a growth of yeast that causes the appearance of the banana to be damaged and unfit for consumption. However, ripe bananas that look visually bad still contain high glucose, which can be used in fermentation or advanced processing. One of the solutions to avoid losses due to ripe banana spoilage is to process it into banana sale. Banana sale is a processed product produced from ripe bananas that go through a drying process to reduce the moisture content to a safe level, so that it can extend its shelf life. This drying process can be done by two methods, namely drying in the sun and smoking. The purpose of both methods is to reduce the water content of bananas, so that they are not easily damaged by microorganisms. Using this technique, bananas that are prone to spoilage can be transformed into more durable products, have a distinctive taste, and have a high selling value. The quality of banana sales is influenced by various factors, such as its color, taste, aroma, texture, and shelf life. By processing bananas for sale, their economic value can increase significantly. Farmers can not only reduce losses due to bananas that do not sell well in the fresh market, but also earn additional income from value-added processed products. Banana sale products have great potential to be developed as one of the processed food products that have economic value and are beneficial to the community (Masuku, M. A., 2023; Lestari, S., et al., 2024).